(untitled) (LETRAS, 2014)
El estudio aborda el tema de la dictadora en La dama de cristal (1999), de Zelmar Acevedo Díaz (Argentina, 1951). Se comparan con otras novelas sobre el mismo tema y se examinan coincidencias o disparidades entre la representación literaria femenina y masculina del autoritarismo. La dictadura latinoamericana como fenómeno político ha persistido en América Latina con diferentes matices ideológicos. Gabriel García Márquez en El otoño del patriarca, Mario Vargas Llosa en La fiesta del Chivo o Luis Spota en El tiempo de la ira tratan este hecho para perfilar sus rasgos distintivos. Existe un caso particular en que el autoritarismo lo encarna una mujer. This study focuses on the theme of female dictator in La dama de cristal (1999), by Zelmar Acevedo Díaz (Argentina, 1951). It is compared with other novels on the same theme and an analysis is carried out of coincidences or disparities between the feminine and masculine literary representation of authoritarianism. Latin American dictatorships are a political phenomenon that has persisted in Latin America with different ideological tones. Gabriel García Márquez in El otoño del patriarca; Mario Vargas Llosa in La fiesta del Chivo or Luis Spota in El tiempo de la ira have approached this issue to profile its distinctive features. There is one particular case of a female dictator.